Does atmospheric CO2 seasonality play an important role in governing the air-sea flux of CO2? - P. R. Halloran (Biogeosciences, 2012)
The amplitude, phase, and form of the seasonal cycle of atmospheric CO2 concentrations varies on many time and space scales (Peters et al., 2007). Intra-annual CO2 variation is primarily driven by seasonal uptake and release of CO2 by the terrestrial biosphere (Machta et al., 1977; Buchwitz et al., 2007), with a small (Cadule et al., 2010; Heimann et al., 1998), but potentially changing (Gorgues et al., 2010) contribution from the ocean. Variability in the magnitude, spatial distribution, and seasonal drivers of terrestrial net primary productivity (NPP) will be induced by, amongst other factors, anthropogenic CO2 release (Keeling et al., 1996), land-use change (Zimov et al., 1999) and planetary orbital variability, and will lead to changes in CO2atm seasonality. Despite CO2atm seasonality being a dynamic and prominent feature of the Earth System, its potential to drive changes in the air-sea flux of CO2 has not previously (to the best of my knowledge) been explored. It is important that we investigate the impact of CO2atm seasonality change, and the potential for carbon-cycle feedbacks to operate through the modification of the CO2atm seasonal cycle, because the decision had been made to prescribe CO2atm concentrations (rather than emissions) within model simulations for the fifth IPCC climate assessment (Taylor et al., 2009). In this study I undertake ocean-model simulations within which different magnitude CO2atm seasonal cycles are prescribed. These simulations allow me to examine the effect of a change in CO2atm seasonal cycle magnitude on the air-sea CO2 flux. I then use an off-line model to isolate the drivers of the identified air-sea CO2 flux change, and propose mechanisms by which this change may come about. Three mechanisms are identified by which co-variability of the seasonal cycles in atmospheric CO2 concentration, and seasonality in sea-ice extent, wind-speed and ocean temperature, could potentially lead to changes in the air-sea flux of CO2 at mid-to-high latitudes. The sea-ice driven mechanism responds to an increase in CO2atm seasonality by pumping CO2 into the ocean, the wind-speed and solubility-driven mechanisms, by releasing CO2 from the ocean (in a relative sense). The relative importance of the mechanisms will be determined by, amongst other variables, the seasonal extent of sea-ice. To capture the described feedbacks within earth system models, CO2atm concentrations must be allowed to evolve freely, forced only by anthropogenic emissions rather than prescribed CO2atm concentrations; however, time-integrated ocean simulations imply that the cumulative net air-sea flux could be at most equivalent to a few ppm CO2atm. The findings presented here suggest that, at least under pre-industrial conditions, the prescription of CO2atm concentrations rather than emissions within simulations will have little impact on the marine anthropogenic CO2 sink.